Preservative film as well as preparation method and application thereof

Through the composite plastic wrap that combines ascorbic acid carbon quantum dots and chitosan, the high respiration rate and easy browning of fruits such as lychee is solved, effective preservation effect is achieved, and good antibacterial, antioxidant and anti-ultraviolet properties are provided.

CN119409998APending Publication Date: 2025-02-11SOUTH CHINA AGRICULTURAL UNIVERSITY

Patent Information

Application Number
CN202411315435.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

The existing technology is difficult to effectively preserve fruits such as lychees with high respiration rates and browning. Traditional refrigeration and chemical preservatives have problems with high energy consumption and potential health risks.

Method used

A composite plastic wrap with ascorbic acid quantum dots combined with chitosan is used to prepare carbon carbon dioxide dots ascorbic acid quantum dots through hydrothermal reaction, and mixed with acetic acid solution of chitosan to form a film forming solution to prepare plastic wrap.

Benefits of technology

This plastic wrap can effectively inhibit the growth of mold in fruits, reduce weight loss rate, slow down the degradation of soluble solids, prolong the shelf life of fruits, and has good antibacterial, antioxidant and anti-ultraviolet properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119409998A_ABST
    Figure CN119409998A_ABST
Patent Text Reader

Abstract

The invention discloses a preservative film as well as a preparation method and application thereof, and the preparation method comprises the following steps: preparing ascorbic acid carbon quantum dots; preparing an acetic acid solution of chitosan; the ascorbic acid carbon quantum dots and an acetic acid solution of chitosan are mixed to obtain a film forming solution, and the film forming solution is dried to form the preservative film. The preservative film prepared by the invention is used for fruit preservation, and can inhibit the growth of mould in fruits, reduce the weight loss ratio of the fruits, slow down the reduction of soluble solids in the fruits, and realize a better fruit preservation effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of food preservation, and more particularly to a fresh-keeping film and a preparation method and application thereof. Background Art

[0002] Traditional methods of fruit preservation mainly rely on refrigeration technology and chemical preservatives. Refrigeration requires special equipment, which increases energy consumption and costs; chemical preservatives may cause residue problems, posing potential risks to human health and the environment.

[0003] With the continuous research and breakthroughs in fruit preservation, packaging fruits with plastic wrap can not only reduce costs and avoid toxic effects, but also improve the antibacterial properties of fruits and ensure food safety.

[0004] Carbon quantum dots are a type of spherical zero-dimensional nanomaterials with a size less than 10nm. As an emerging nanomaterial, it has shown a wide range of application potential due to its extremely small size and special optoelectronic properties. In recent years, scientific researchers have used the excellent performance of carbon quantum dots to add them to plastic wrap to conduct preservation experiments on fruits. For example, using pith wood as a carbon source, a pith wood carbon dot-polyvinyl alcohol composite film was prepared to extend the shelf life of strawberries; using kelp as a carbon source, carbon quantum dots were prepared by a hydrothermal method, and then carbon quantum dots, ascorbic acid, citric acid, calcium chloride and chitosan were compounded to prepare a nano coating agent to preserve mangoes; using glucose as a carbon source, carbon quantum dots were prepared, mixed with a cellulose nanofiber solution to form a composite plastic wrap solution, which was used to preserve citrus.

[0005] However, the above-mentioned carbon quantum dots and the plastic wrap formed by them are only effective for specific types of fruits and are not universally applicable. For example, for the preservation of lychees, since lychees have a high respiration rate and are prone to browning, the preservation requirements of lychees are higher than those of other fruits. It is necessary to seek new plastic wrap technology to achieve the preservation of lychees. Summary of the invention

[0006] In view of the above technical problems, the present invention provides a fresh-keeping film and a preparation method and application thereof. The prepared fresh-keeping film is used for fruit preservation, can inhibit the growth of mold in the fruit, reduce the weight loss rate of the fruit, slow down the reduction of soluble solids in the fruit, and achieve better fruit preservation effect.

[0007] In order to achieve the above objectives, this application adopts the following technical solutions:

[0008] A method for preparing a fresh-keeping film, comprising:

[0009] Preparation of ascorbic acid carbon quantum dots;

[0010] preparing an acetic acid solution of chitosan;

[0011] The ascorbic acid carbon quantum dots and the acetic acid solution of chitosan are mixed to obtain a film-forming liquid, and the film-forming liquid is dried to form a fresh-keeping film.

[0012] The preparation method of the present application is simple and convenient. The ascorbic acid and chitosan used are both natural raw materials and are pollution-free to the environment. The prepared ascorbic acid carbon quantum dots-chitosan composite cling film has good anti-ultraviolet, antioxidant, antibacterial and preservation properties.

[0013] Furthermore, the preparation method of the ascorbic acid carbon quantum dots comprises: subjecting an ascorbic acid solution to a hydrothermal reaction, filtering and dialyzing after cooling to obtain the ascorbic acid carbon quantum dots.

[0014] The reactor required for the hydrothermal reaction is much simpler than other methods, the cost is relatively low, and the reaction operation is relatively simple. The preparation of ascorbic acid carbon quantum dots at 160-260°C is conducive to the decomposition of the carbon source and the rearrangement of carbon atoms, thereby forming ascorbic acid carbon quantum dots with specific structures and properties. At the same time, the reaction time of 4-14h is conducive to the full growth of ascorbic acid carbon quantum dots, thereby obtaining ascorbic acid carbon quantum dots of suitable size and crystallinity. Filtration and dialysis are used to remove small molecule impurities and unreacted ascorbic acid, improve the purity and stability of ascorbic acid carbon quantum dots, and ensure their consistent and reliable performance in subsequent applications.

[0015] Furthermore, the concentration of the ascorbic acid solution is 0.04-0.06 g / mL; the temperature of the hydrothermal reaction is 160° C. to 260° C.; and the reaction time of the hydrothermal reaction is 4 h to 14 h.

[0016] Furthermore, the method for preparing the chitosan acetic acid solution comprises: firstly dissolving chitosan in an aqueous solution of acetic acid, and then adding glycerol; and heating and stirring in a water bath to prepare the chitosan acetic acid solution.

[0017] Furthermore, the mass fraction of acetic acid in the aqueous solution of acetic acid is 1wt% to 2wt%; the mass ratio of glycerol to chitosan is 0.3-0.4:1; and the temperature of the water bath heating is 80°C to 95°C.

[0018] In the present application, chitosan is insoluble in water, and the acidic environment protonates the amino groups on the chitosan molecular chain to form positively charged ammonium ions, which weaken the hydrogen bonds between the molecular chains and increase the molecular distance, so that water molecules can intervene and promote the dissolution of chitosan; and 1%-2% mass fraction of acetic acid can minimize the acidic odor after film formation. 30%-40% glycerol can improve the flexibility and ductility of the chitosan film and improve its mechanical properties. Stirring in a water bath at 80℃-95℃ for 2-3h can fully dissolve the chitosan by accelerating the molecular thermal motion.

[0019] Furthermore, the acetic acid solution of ascorbic acid carbon quantum dots and chitosan is stirred at a temperature of 75° C. to 80° C. to obtain a film-forming solution, and the film-forming solution is dried at a temperature of 75° C. to 80° C. to form a fresh-keeping film.

[0020] In the present application, the acetic acid solution of ascorbic acid carbon quantum dots and chitosan is stirred at 75°C to 80°C for 30 to 40 minutes, and the two are mixed evenly by accelerating the molecular thermal motion. The film-forming solution is placed in an oven at 75°C to 80°C and dried for 6 to 8 hours, which can fully evaporate the water and form an ascorbic acid carbon quantum dot-chitosan composite cling film. In the process of preparing cling film, it is very important to use appropriate drying temperature and time, because this directly affects the final performance and use effect of the cling film. The drying temperature of 75°C-80°C can effectively remove moisture from the cling film while avoiding deformation or damage of the material caused by excessive temperature. The drying time of 6-8 hours can ensure that the cling film is completely dry, thereby ensuring its stability and durability during use.

[0021] The present application also provides a fresh-keeping film, which is prepared based on the preparation method described above.

[0022] An application of a fresh-keeping film, wherein the fresh-keeping film as described above is used for preserving fruits.

[0023] Furthermore, the water-retaining fruit is one or more of strawberry, blueberry, grape, and citrus.

[0024] Lychees, strawberries, blueberries, grapes or citrus fruits are all very easy to corrupt and difficult to keep fresh. The present application can effectively extend the shelf life of lychees, strawberries, blueberries, grapes or citrus fruits and slow down their corruption. Among them, the challenge of keeping lychees fresh is its high respiration rate and easy browning, which makes it more difficult to keep fresh than other fruits. The present application can effectively inhibit the respiration of lychees, prevent the invasion of pathogenic microorganisms, and delay the occurrence of corruption.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. Different raw materials and preparation methods will lead to differences in the properties and applications of carbon dots. This application applies ascorbic acid carbon quantum dots to cling film. Under visible light irradiation, the strong oxidative hydroxyl radicals and ketone radicals produced by ascorbic acid carbon quantum dots can penetrate the cell wall of bacteria, enter the bacteria, block their respiratory system and electron transport system, and effectively kill bacteria. Chitosan has good antibacterial properties. The combination of ascorbic acid carbon quantum dots and chitosan can prevent the invasion of pathogenic microorganisms and delay the occurrence of fruit rot. The cling film of this application can effectively inhibit the cell activity of Escherichia coli and Staphylococcus aureus.

[0027] 2. When ascorbic acid carbon quantum dots are combined with chitosan to form a composite cling film, they also have excellent optical properties. In particular, ascorbic acid carbon quantum dots have the ability to absorb and scatter ultraviolet rays, which can significantly enhance the anti-ultraviolet performance of the cling film. In addition, ascorbic acid is rich in carbon and is a natural food antioxidant, which is beneficial for removing free radicals in fruits. The above characteristics make the ascorbic acid carbon quantum dots-chitosan composite cling film have the characteristics of anti-browning, improving the water retention and freshness of fruits, slowing down the nutrient loss rate of fruits, reducing the reduction rate of soluble solids, and slowing down the decline rate of vitamin C content. By combining the two to form a protective cling film, the water loss of fruits is reduced, the respiration of fruits is inhibited, and it has good freshness-keeping performance.

[0028] 3. Ascorbic acid and chitosan are both natural active substances with excellent biodegradability. The prepared ascorbic acid carbon quantum dots-chitosan composite cling film is environmentally friendly and low-cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0030] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0031] In the attached figure:

[0032] Figure 1 :a is the infrared curve of ascorbic acid carbon quantum dots; b is the ultraviolet absorption spectrum of ascorbic acid carbon quantum dots; c is the free radical scavenging rate of ascorbic acid carbon quantum dots on DPPH; d is the maximum excitation spectrum and maximum emission spectrum of ascorbic acid carbon quantum dots; e is the antibacterial curve of ascorbic acid carbon quantum dots against Escherichia coli and Staphylococcus aureus;

[0033] Figure 2 : a is the infrared curve of the cling film in this application; b is the ultraviolet transmittance of the cling film in this application; c is the ABTS free radical scavenging rate of the cling film in this application; d is the absorbance curve of the cling film in this application;

[0034] Figure 3 The results of preservation of litchi appearance in different treatment groups;

[0035] Figure 4 It is the curve diagram of the weight loss rate of litchi in different treatment groups;

[0036] Figure 5 is the change curve of soluble solids in litchi of different treatment groups;

[0037] Figure 6 This is a curve chart showing the changes in vitamin C content in litchi in different treatment groups. DETAILED DESCRIPTION

[0038] The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. Modifications or substitutions made to the methods, steps or conditions of the present invention without departing from the spirit and essence of the present invention are within the scope of protection of the present invention. Unless otherwise specified, the experimental materials, reagents, instruments, etc. used in the examples of the present invention are all commercially available; unless otherwise specified, all technical means in the examples of the present invention are conventional means well known to those skilled in the art.

[0039] The present application provides a method for preparing a fresh-keeping film, comprising:

[0040] S1: preparing ascorbic acid carbon quantum dots; specifically comprising:

[0041] Ascorbic acid is added to deionized water, and an ascorbic acid solution is formed by stirring and ultrasonication; wherein the concentration of the ascorbic acid solution is 0.04-0.06 g / mL. The ultrasonication time is between 5 min and 10 min, and ultrasound effectively improves the dissolution rate and efficiency by accelerating molecular motion, cavitation effect and dispersion.

[0042] The ascorbic acid solution is transferred to a stainless steel autoclave of polytetrafluoroethylene for a hydrothermal reaction; wherein the temperature of the hydrothermal reaction is 160°C to 260°C, and the reaction time of the hydrothermal reaction is 4h to 14h. The preparation of ascorbic acid carbon quantum dots at 160-260°C is conducive to the decomposition of the carbon source and the rearrangement of carbon atoms, thereby forming ascorbic acid carbon quantum dots with specific structures and properties, while the reaction time of 4-14h is conducive to the full growth of ascorbic acid carbon quantum dots, thereby obtaining ascorbic acid carbon quantum dots of suitable size and crystallinity.

[0043] After the reaction, the solution is cooled and filtered and dialyzed to obtain the ascorbic acid carbon quantum dots. Filtration and dialysis are used to remove small molecule impurities and unreacted ascorbic acid, improve the purity and stability of the ascorbic acid carbon quantum dots, and ensure that they have consistent and reliable performance in subsequent applications.

[0044] S2: preparing an acetic acid solution of chitosan; specifically comprising:

[0045] Firstly, chitosan is dissolved in an aqueous solution of acetic acid, wherein the mass fraction of acetic acid in the aqueous solution of acetic acid is 1wt% to 2wt%.

[0046] Then add glycerol; the mass ratio of glycerol to chitosan is 0.3-0.4:1;.

[0047] The chitosan acetic acid solution is prepared by heating in a water bath and stirring. The water bath heating temperature is 80° C. to 95° C., and the stirring is performed while heating in the water bath. The reaction is continued for 2 to 3 hours to prepare the chitosan acetic acid solution with a mass percentage of 1% to 2%.

[0048] Chitosan is insoluble in water, and the acidic environment protonates the amino groups on the chitosan molecular chain to form positively charged ammonium ions, which weaken the hydrogen bonds between the molecular chains and increase the molecular distance, allowing water molecules to intervene and promote the dissolution of chitosan; and 1%-2% mass fraction of acetic acid can minimize the acidic odor after film formation. 30%-40% glycerol can improve the flexibility and ductility of the chitosan film and improve its mechanical properties. Stirring in a water bath at 80℃-95℃ for 2-3h can fully dissolve chitosan by accelerating the thermal motion of molecules.

[0049] S3: The ascorbic acid carbon quantum dots and the acetic acid solution of chitosan are mixed to obtain a film-forming solution, and the film-forming solution is dried to form a fresh-keeping film.

[0050] The acetic acid solution of ascorbic acid carbon quantum dots and chitosan is stirred at 75°C to 80°C for 30 to 40 minutes to accelerate the molecular thermal motion so that the two are evenly mixed to obtain a film-forming solution. The film-forming solution is dried in an oven at 75°C to 80°C for 6 to 8 hours to fully evaporate the water and form a fresh-keeping film.

[0051] The present application also provides a fresh-keeping film, which is prepared based on the preparation method described above.

[0052] The present application also provides an application of a plastic wrap, wherein the plastic wrap as described above is used for preserving fruits, and the fruits are one or more of strawberries, blueberries, grapes, and citrus.

[0053] Example 1 Preparation of ascorbic acid carbon quantum dots-chitosan composite cling film

[0054] S1: Weigh 1 g of ascorbic acid, transfer to a 50 mL beaker, add 20 mL of deionized water, stir with a glass rod for 3 min, then put it into an ultrasonic machine for 10 min to completely dissolve the solution; transfer the solution to a 100 mL polytetrafluoroethylene stainless steel autoclave, place it in an oven, and heat at 160 ° C for 14 h;

[0055] After cooling naturally to room temperature, the residue was first filtered out by coarse filtration, then filtered with a 0.22 μm filter membrane, and then dialyzed with a 500D dialysis bag for 6 h to obtain ascorbic acid carbon quantum dots;

[0056] S2: 6 g of chitosan was dissolved in 200 mL of 1.5% acetic acid aqueous solution, 40% of the weight of chitosan glycerol was added, and the mixture was stirred in a water bath at 95° C. for 3 h to prepare a 1.5% chitosan acetic acid solution;

[0057] S3: dilute the ascorbic acid carbon quantum dots prepared in S1 with deionized water by 1, 1.25, 2.5, 5, 10, and 20 times respectively to prepare carbon quantum dot solutions with dilution times of 1, 1.25, 2.5, 5, 10, and 20; add 100 mL of the diluted carbon quantum dot solution to the acetic acid solution of chitosan prepared in S2; stir at 80°C for 30 minutes to prepare film-forming solutions with dilution times of 1, 1.25, 2.5, 5, 10, and 20;

[0058] 300 mL of film-forming liquid with dilution multiples of 1, 1.25, 2.5, 5, 10, and 20 were respectively poured into the mold, and placed in an oven at 80°C to dry for 6 hours to obtain plastic wrap with dilution multiples of 1, 1.25, 2.5, 5, 10, and 20.

[0059] Example 2 Preparation of ascorbic acid carbon quantum dots-chitosan composite cling film

[0060] S1: Weigh 2 g of ascorbic acid, transfer to a 100 mL beaker, add 40 mL of deionized water, stir with a glass rod for 3 min, then put it into an ultrasonic machine for 10 min to completely dissolve the solution; transfer the solution to a 100 mL polytetrafluoroethylene stainless steel autoclave, place it in an oven, and heat at 180 ° C for 12 h;

[0061] After cooling naturally to room temperature, the residue was first filtered out by coarse filtration, then filtered with a 0.22 μm filter membrane, and then dialyzed with a 500D dialysis bag for 6 h to obtain ascorbic acid carbon quantum dots;

[0062] S2: 6 g of chitosan was dissolved in 200 mL of 1.5% acetic acid aqueous solution, 40% of the weight of chitosan glycerol was added, and the mixture was stirred in a water bath at 95° C. for 3 h to prepare a 1.5% chitosan acetic acid solution;

[0063] S3: dilute the ascorbic acid carbon quantum dots prepared in S1 with deionized water by 1, 1.25, 2.5, 5, 10, and 20 times respectively to prepare carbon quantum dot solutions with dilution times of 1, 1.25, 2.5, 5, 10, and 20; add 100 mL of the diluted carbon quantum dot solution to the acetic acid solution of chitosan prepared in S2; stir at 80°C for 30 minutes to prepare film-forming solutions with dilution times of 1, 1.25, 2.5, 5, 10, and 20;

[0064] 300 mL of film-forming liquid with dilution multiples of 1, 1.25, 2.5, 5, 10, and 20 were respectively poured into the mold, and placed in an oven at 80°C to dry for 6 hours to obtain plastic wrap with dilution multiples of 1, 1.25, 2.5, 5, 10, and 20.

[0065] Example 3 Preparation of ascorbic acid carbon quantum dots-chitosan composite cling film

[0066] S1: Weigh 3 g of ascorbic acid, transfer to a 100 mL beaker, add 60 mL of deionized water, stir with a glass rod for 3 min, then put it into an ultrasonic machine for 10 min to completely dissolve the solution; transfer the solution to a 100 mL polytetrafluoroethylene stainless steel autoclave, place it in an oven, heat at 200 ° C for 10 h;

[0067] After cooling naturally to room temperature, the residue was first filtered out by coarse filtration, then filtered with a 0.22 μm filter membrane, and then dialyzed with a 500D dialysis bag for 6 h to obtain ascorbic acid carbon quantum dots;

[0068] S2: 6 g of chitosan was dissolved in 200 mL of 1.5% acetic acid aqueous solution, 40% of the weight of chitosan glycerol was added, and the mixture was stirred in a water bath at 95° C. for 3 h to prepare a 1.5% chitosan acetic acid solution;

[0069] S3: dilute the ascorbic acid carbon quantum dots prepared in S1 with deionized water by 1, 1.25, 2.5, 5, 10, and 20 times respectively to prepare carbon quantum dot solutions with dilution times of 1, 1.25, 2.5, 5, 10, and 20; add 100 mL of the diluted carbon quantum dot solution to the acetic acid solution of chitosan prepared in S2; stir at 80°C for 30 minutes to prepare film-forming solutions with dilution times of 1, 1.25, 2.5, 5, 10, and 20;

[0070] 300 mL of film-forming liquid with dilution multiples of 1, 1.25, 2.5, 5, 10, and 20 were respectively poured into the mold, and placed in an oven at 80°C to dry for 6 hours to obtain plastic wrap with dilution multiples of 1, 1.25, 2.5, 5, 10, and 20.

[0071] Among them, Figure 1 and Figure 2 As shown, Figure 1Schematic diagram of the performance test of ascorbic acid carbon quantum dots obtained in step S1 of this embodiment. Wherein: a is the infrared curve of ascorbic acid carbon quantum dots; b is the ultraviolet absorption spectrum of ascorbic acid carbon quantum dots; c is the free radical scavenging rate of ascorbic acid carbon quantum dots to DPPH; d is the maximum excitation spectrum and maximum emission spectrum of ascorbic acid carbon quantum dots; e is the antibacterial curve of ascorbic acid carbon quantum dots to Escherichia coli and Staphylococcus aureus. It can be seen that the infrared curve of ascorbic acid carbon quantum dots shows that ascorbic acid carbon quantum dots have only two characteristic absorption peaks, the structure is relatively pure, and the polyhydroxyl groups in the raw materials are retained. Ascorbic acid carbon quantum dots show strong absorption capacity in the ultraviolet region (200-380nm). In addition, ascorbic acid carbon quantum dots not only have strong antioxidant properties, but also have antibacterial properties that inhibit the growth of Escherichia coli and Staphylococcus aureus.

[0072] Figure 2 It is a performance test diagram of the cling film in step S3 of this embodiment. Wherein: a is the infrared curve of the cling film composited with ascorbic acid carbon quantum dots and chitosan; b is the ultraviolet transmittance of the cling film composited with ascorbic acid carbon quantum dots and chitosan; c is the free radical scavenging rate of the cling film composited with ascorbic acid carbon quantum dots and chitosan for ABTS; d is the XRD curve of the cling film composited with ascorbic acid carbon quantum dots and chitosan. It can be seen that the infrared spectra of all chitosan films with different concentrations of ascorbic acid carbon quantum dots added only have changes in peak intensity, and the frequency region of the spectrum has not changed, indicating that carbon quantum dots and chitosan polymer matrix form compatible films. With the increase of the concentration of ascorbic acid carbon quantum dots, the intensity of the XRD diffraction peak gradually weakens, forming a larger amorphous feature, indicating that some regular arrangements of chitosan molecules are disrupted by carbon quantum dots. Pure chitosan film has almost no blocking ability for ultraviolet rays (200-380nm), while the ultraviolet transmittance of chitosan cling film with ascorbic acid carbon quantum dots is significantly reduced. The addition of low-concentration ascorbic acid carbon quantum dots can greatly improve the ABTS scavenging activity of pure chitosan film, and the scavenging activity increases significantly with the increase of ascorbic acid carbon quantum dots concentration.

[0073] Combination Figure 1 and Figure 2 It can be seen that ascorbic acid carbon quantum dots and chitosan matrix form a compatible cling film, and with the addition of ascorbic acid carbon quantum dots, the anti-ultraviolet, antioxidant and antibacterial properties of the cling film are improved on the basis of the chitosan matrix.

[0074] Example 4 Preparation of ascorbic acid carbon quantum dots-chitosan composite cling film

[0075] S1: Weigh 4 g of ascorbic acid, transfer to a 50 mL beaker, add 80 mL of deionized water, stir with a glass rod for 3 min, then put it into an ultrasonic machine for 10 min to completely dissolve the solution; transfer the solution to a 100 mL polytetrafluoroethylene stainless steel autoclave, place it in an oven, heat at 220 ° C for 8 h;

[0076] After cooling naturally to room temperature, the residue was first filtered out by coarse filtration, then filtered with a 0.22 μm filter membrane, and then dialyzed with a 500D dialysis bag for 6 h to obtain ascorbic acid carbon quantum dots;

[0077] S2: 6 g of chitosan was dissolved in 200 mL of 1.5% acetic acid aqueous solution, 40% of the weight of chitosan glycerol was added, and the mixture was stirred in a water bath at 95° C. for 3 h to prepare a 1.5% chitosan acetic acid solution;

[0078] S3: dilute the ascorbic acid carbon quantum dots prepared in S1 with deionized water by 1, 1.25, 2.5, 5, 10, and 20 times respectively to prepare carbon quantum dot solutions with dilution times of 1, 1.25, 2.5, 5, 10, and 20; add 100 mL of the diluted carbon quantum dot solution to the acetic acid solution of chitosan prepared in S2; stir at 80°C for 30 minutes to prepare film-forming solutions with dilution times of 1, 1.25, 2.5, 5, 10, and 20;

[0079] 300 mL of film-forming liquid with dilution multiples of 1, 1.25, 2.5, 5, 10, and 20 were respectively poured into the mold, and placed in an oven at 80°C to dry for 6 hours to obtain plastic wrap with dilution multiples of 1, 1.25, 2.5, 5, 10, and 20.

[0080] Example 5 Preparation of ascorbic acid carbon quantum dots-chitosan composite cling film

[0081] S1: Weigh 5 g of ascorbic acid, transfer to a 150 mL beaker, add 100 mL of deionized water, stir with a glass rod for 3 min, then put it into an ultrasonic machine for 10 min to completely dissolve the solution; transfer the solution to a 100 mL polytetrafluoroethylene stainless steel autoclave, place it in an oven, heat at 240 ° C for 6 h;

[0082] After cooling naturally to room temperature, the residue was first filtered out by coarse filtration, then filtered with a 0.22 μm filter membrane, and then dialyzed with a 500D dialysis bag for 6 h to obtain ascorbic acid carbon quantum dots;

[0083] S2: 6 g of chitosan was dissolved in 200 mL of 1.5% acetic acid aqueous solution, 40% of the weight of chitosan glycerol was added, and the mixture was stirred in a water bath at 95° C. for 3 h to prepare a 1.5% chitosan acetic acid solution;

[0084] S3: dilute the ascorbic acid carbon quantum dots prepared in S1 with deionized water by 1, 1.25, 2.5, 5, 10, and 20 times respectively to prepare carbon quantum dot solutions with dilution times of 1, 1.25, 2.5, 5, 10, and 20; add 100 mL of the diluted carbon quantum dot solution to the acetic acid solution of chitosan prepared in S2; stir at 80°C for 30 minutes to prepare film-forming solutions with dilution times of 1, 1.25, 2.5, 5, 10, and 20;

[0085] 300 mL of film-forming liquid with dilution multiples of 1, 1.25, 2.5, 5, 10, and 20 were respectively poured into the mold, and placed in an oven at 80°C to dry for 6 hours to obtain plastic wrap with dilution multiples of 1, 1.25, 2.5, 5, 10, and 20.

[0086] Example 6 Preparation of ascorbic acid carbon quantum dots-chitosan composite cling film

[0087] S1: Weigh 6 g of ascorbic acid, transfer to a 150 mL beaker, add 120 mL of deionized water, stir with a glass rod for 3 min, then put it into an ultrasonic machine for 10 min to completely dissolve the solution; transfer the solution to a 100 mL polytetrafluoroethylene stainless steel autoclave, place it in an oven, and heat at 260 ° C for 4 h;

[0088] After cooling naturally to room temperature, the residue was first filtered out by coarse filtration, then filtered with a 0.22 μm filter membrane, and then dialyzed with a 500D dialysis bag for 6 h to obtain ascorbic acid carbon quantum dots;

[0089] S2: 6 g of chitosan was dissolved in 200 mL of 1.5% acetic acid aqueous solution, 40% of the weight of chitosan glycerol was added, and the mixture was stirred in a water bath at 95° C. for 3 h to prepare a 1.5% chitosan acetic acid solution;

[0090] S3: dilute the ascorbic acid carbon quantum dots prepared in S1 with deionized water by 1, 1.25, 2.5, 5, 10, and 20 times respectively to prepare carbon quantum dot solutions with dilution times of 1, 1.25, 2.5, 5, 10, and 20; add 100 mL of the diluted carbon quantum dot solution to the acetic acid solution of chitosan prepared in S2; stir at 80°C for 30 minutes to prepare film-forming solutions with dilution times of 1, 1.25, 2.5, 5, 10, and 20;

[0091] 300 mL of film-forming liquid with dilution multiples of 1, 1.25, 2.5, 5, 10, and 20 were respectively poured into the mold, and placed in an oven at 80°C to dry for 6 hours to obtain plastic wrap with dilution multiples of 1, 1.25, 2.5, 5, 10, and 20.

[0092] Comparative Example 1 Preparation of Chitosan Fresh-keeping Film

[0093] S1: 6 g of chitosan was dissolved in 200 mL of 1.5% acetic acid aqueous solution, 40% of the weight of chitosan glycerol was added, and the mixture was stirred in a water bath at 95° C. for 3 h to prepare a 1.5% chitosan acetic acid solution;

[0094] S3: Pour 300 mL of chitosan acetic acid solution into a mold, put it into an oven at 80° C. and dry it for 6 hours to obtain a chitosan preservative film.

[0095] Experimental Example: Application of Ascorbic Acid Carbon Quantum Dots-Chitosan Composite Cling Film to Litchi Preservation

[0096] In this embodiment, Huaizhi lychees picked in Nanshan, Shenzhen are used. The fruits are 90% mature, and fresh fruits with comparable maturity, no pests or diseases, and no mechanical damage are selected.

[0097] (1) Sample grouping:

[0098] The litchis were divided into five groups, each with 40 fruits, and were named CK, CS, CDs1 / CS, CDs2 / CS, and CDs3 / CS. The treatments were as follows:

[0099] CK (blank): 40 lychees were placed in 40 airline cups without any other treatment and placed in a room at 28°C.

[0100] CS (Chitosan): 40 lychees were placed in 40 airline cups respectively, sealed with the plastic wrap containing only chitosan in Comparative Example 1, and placed in a room at 28°C.

[0101] CDs1 / CS (the preservative film with a dilution factor of 5 in Example 3): 40 lychees were placed in 40 aviation cups respectively, sealed with the preservative film with a dilution factor of 5 prepared in Example 3, and placed in a room at 28°C.

[0102] CDs2 / CS (the preservative film with a dilution factor of 2.5 in Example 3): 40 lychees were placed in 40 aviation cups respectively, sealed with the preservative film with a dilution factor of 2.5 prepared in Example 2, and placed in a room at 28°C.

[0103] CDs3 / CS (the preservative film with a dilution factor of 1.25 in Example 3): 40 lychees were placed in 40 aviation cups respectively, sealed with the preservative film with a dilution factor of 1.25 prepared in Example 3, and placed in a room at 28°C.

[0104] (2) Effect measurement:

[0105] The appearance, weight loss rate, soluble solids and vitamin C content of litchi were measured on the 1st, 3rd, 5th, 7th, 9th and 11th day during the storage process to reflect the freshness of litchi.

[0106] Determination of litchi appearance: Observe the appearance of the samples and take photos on the 1st, 3rd, 5th, 7th, 9th and 11th days respectively.

[0107] Determination of litchi weight loss rate: Weigh the litchi on the first day, and take samples from each group on the third, fifth, seventh, ninth and eleventh days to weigh the fruit weight after storage to calculate the weight loss rate. The calculation formula is as follows:

[0108]

[0109] Determination of soluble solids in litchi: The refractive index of each group of litchi juice was measured on the 1st, 3rd, 5th, 7th, 9th and 11th day using a handheld saccharimeter.

[0110] Determination of vitamin C content: The determination of vitamin C uses ultraviolet spectrophotometry. Weigh 10 mg of ascorbic acid (accurate to 0.1 mg), dissolve it with 2% metaphosphoric acid, transfer it to a 100 mL volumetric flask, dilute it to the mark with metaphosphoric acid, and mix it. The concentration of this ascorbic acid solution is 100 μg / mL. Take 0.00, 0.10, 0.20, 0.40, 0.60, 0.80, 1.00, and 1.20 mL of ascorbic acid standard solution and place it in a 15 mL test tube; make up to volume with 2% metaphosphoric acid, shake it well, and prepare ascorbic acid solutions with concentrations of 0.00, 1.00, 2.00, 4.00, 6.00, 8.00, 10.0, and 12.0 μg / mL, respectively. Using pure water as a reference, use a quartz cuvette to measure the absorbance of the standard series of ascorbic acid solutions at a wavelength of 243 nm. A standard curve was drawn with a series of standard vitamin C (0.00, 1.00, 2.00, 4.00, 6.00, 8.00, 10.0, 12.0 μg / mL) as the abscissa and the corresponding absorbance as the ordinate to obtain the regression equation.

[0111] Preparation of sample solution: Weigh 2-5g of the edible part of each litchi sample, crush it, add 20mL of extractant, and ultrasonicate for 30min. Take 2mL of solution, dilute it 10 times with the extractant, and shake well.

[0112] Determination of sample solution: Take 0.5mL of extract from each group, add 6 drops of 0.5mol / L sodium hydroxide solution, mix in a 15mL test tube, place at room temperature for 40 minutes, add 2% metaphosphoric acid and dilute 20 times, then shake well. Using pure water as a reference, measure its absorbance at a wavelength of 243nm, and substitute it into the regression equation to obtain the vitamin C content. The calculation method is as follows,

[0113] Vitamin C content:

[0114] Where:

[0115] 200: dilution factor for sample preparation;

[0116] 20: dilution multiple of sample solution during measurement;

[0117] C: The ascorbic acid content, μg / mL, was obtained from the calibration curve.

[0118] (3) Results analysis

[0119] 1) The appearance of litchi in different treatment groups is as follows Figure 3 Shown

[0120] Depend on Figure 3 It can be seen that the CK group and CS group without ascorbic acid carbon quantum dots were corrupt and moldy earlier, and a large number of molds were bred on the eleventh day, while the CDs1 / CS, CDs2 / CS and CDs3 / CS groups with ascorbic acid carbon quantum dots had only a small amount of mold, proving that the cling film with ascorbic acid carbon quantum dots can greatly improve the preservation function of litchi.

[0121] 2) The results of litchi weight loss rate in different treatment groups are shown in Table 1 and Figure 4 As shown by Figure 4 As shown in Table 1, during the storage period, the weight loss rate of all treatment groups showed an overall downward trend, while the decline rate of the treatment group with ascorbic acid carbon quantum dots was lower, among which CDs2 / CS had the lowest decline rate, proving that the cling film with ascorbic acid carbon quantum dots can enhance the water retention of litchi.

[0122] Table 1 Weight loss rate of litchi in different treatment groups at different times

[0123] Day 3 Day 5 Day 7 Day 9 Day 11 CK 4.14% 4.66% 5.40% 5.97% 7.76% CS 2.85% 3.28% 2.50% 3.77% 5.21% CDs1 / CS 2.87% 3.20% 2.44% 2.98% 3.22% CDs2 / CS 2.60% 3.10% 2.24% 2.26% 3.01% CDs3 / CS 2.80% 3.55% 2.43% 3.33% 3.88%

[0124] 3) The results of litchi soluble solids in different treatment groups are shown in Table 2 and Figure 5 As shown by Figure 5As shown in Table 2, during the storage period, the soluble solids of all treatment groups showed an overall downward trend, with the CK and CS groups decreasing most significantly, decreasing by 47.8% and 44.4% respectively compared with the initial values. The treatment group with added ascorbic acid carbon quantum dots maintained a higher soluble solids value compared with the CK and CS groups, among which CDs2 / CS still had 15.8 soluble solids on the eleventh day, which only decreased by 12.2%, proving that the cling film with added ascorbic acid carbon quantum dots can slow down the decrease of soluble solids of litchi.

[0125] Table 2 Soluble solids of litchi in different treatment groups at different times

[0126] Brix Day 1 Day 3 Day 5 Day 7 Day 9 Day 11 CK 18 16.2 15.8 13.8 12.4 9.4 CS 18 16.4 16.6 15.6 13.2 10 CDs1 / CS 18 16.8 16.2 15 14.6 13.6 CDs2 / CS 18 17.2 17 16.2 16.6 15.8 CDs3 / CS 18 17 16.2 15.4 15 13.4

[0127] 4) The results of vitamin C content of litchi in different treatment groups are shown in Tables 3 and Figure 6 As shown by Figure 6 As shown in Table 3, during the storage period, the vitamin C content of all treatment groups showed a downward trend, while the treatment group with added ascorbic acid carbon quantum dots could maintain more vitamin C compared with the CK group and the CS group. Among them, CDs2 / CS still had 17.76 mg / 100 g on the eleventh day, compared with 11.2 mg / 100 g in the CK group. The rate of decrease of vitamin C content in the CDs2 / CS group was only 63% of the natural state (CK group), which proved that the cling film with added ascorbic acid carbon quantum dots could greatly slow down the decline of vitamin C content in litchi.

[0128] Table 3 Vitamin C content of litchi in different treatment groups at different times

[0129] mg / 100g Day 1 Day 3 Day 5 Day 7 Day 9 Day 11 CK 30.34 24.64 18.33 17.03 15.17 11.20 CS 30.34 25.01 21.62 15.86 14.90 12.70 CDs1 / CS 30.34 24.86 20.75 16.97 15.52 14.73 CDs2 / CS 30.34 27.41 22.44 19.74 18.42 17.76 CDs3 / CS 30.34 24.12 20.78 18.39 16.46 14.71

[0130] Compared with the prior art, the beneficial effects of the present invention are embodied in the following three points:

[0131] 1. Different raw materials and preparation methods will lead to differences in the properties and applications of carbon dots. This application applies ascorbic acid carbon quantum dots to fruit ascorbic acid carbon quantum dots-chitosan composite cling film. Under visible light irradiation, the strong oxidative hydroxyl radicals and ketone radicals produced by ascorbic acid carbon quantum dots can penetrate the cell wall of bacteria, enter the bacteria, block their respiratory system and electron transport system, and effectively kill bacteria. Chitosan has good antibacterial properties. The combination of ascorbic acid carbon quantum dots and chitosan can prevent the invasion of pathogenic microorganisms and delay the occurrence of fruit rot. Experiments have shown that the ascorbic acid carbon quantum dots-chitosan composite cling film of this application can effectively inhibit the cell activity of Escherichia coli and Staphylococcus aureus.

[0132] 2. When ascorbic acid carbon quantum dots are combined with chitosan to form a composite cling film, they also have excellent optical properties. In particular, ascorbic acid carbon quantum dots have the ability to absorb and scatter ultraviolet rays, which can significantly enhance the anti-ultraviolet performance of the cling film. In addition, ascorbic acid is rich in carbon and is a natural food antioxidant, which is beneficial for removing free radicals in fruits. The above characteristics make the ascorbic acid carbon quantum dots-chitosan composite cling film have the characteristics of anti-browning, improving the water retention and freshness of fruits, slowing down the nutrient loss rate of fruits, reducing the reduction rate of soluble solids, and slowing down the decline rate of vitamin C content. By combining the two to form a protective cling film, the water loss of fruits is reduced, the respiration of fruits is inhibited, and it has good freshness-keeping performance.

[0133] 3. Ascorbic acid and chitosan are both natural active substances with excellent biodegradability. The prepared ascorbic acid carbon quantum dots-chitosan composite cling film is environmentally friendly and low-cost.

[0134] It can be understood that the above embodiments only express the preferred implementation modes of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the patent scope of the present invention. It should be pointed out that, for ordinary technicians in this field, without departing from the concept of the present invention, the above technical features can be freely combined, and several deformations and improvements can be made, which all belong to the protection scope of the present invention. Therefore, all equivalent changes and modifications made to the scope of the claims of the present invention should belong to the scope covered by the claims of the present invention.

Claims

1. A method for preparing a fresh-keeping film, characterized in that: include: Preparation of ascorbic acid carbon quantum dots; preparing a chitosan solution in acetic acid; The ascorbic acid carbon quantum dots and the acetic acid solution of chitosan are mixed to obtain a film-forming liquid, and the film-forming liquid is dried to form a fresh-keeping film.

2. The method for preparing a fresh-keeping film according to claim 1, characterized in that: The preparation method of the ascorbic acid carbon quantum dots comprises: subjecting an ascorbic acid solution to a hydrothermal reaction, filtering and dialyzing after cooling to obtain the ascorbic acid carbon quantum dots.

3. The method for preparing a fresh-keeping film according to claim 2, characterized in that: The concentration of the ascorbic acid solution is 0.04-0.06 g / mL; the temperature of the hydrothermal reaction is 160° C. to 260° C.; and the reaction time of the hydrothermal reaction is 4 h to 14 h.

4. The method for preparing a fresh-keeping film according to claim 1, characterized in that: The method for preparing the chitosan acetic acid solution comprises: firstly dissolving chitosan in an acetic acid aqueous solution, then adding glycerol; and heating and stirring in a water bath to prepare the chitosan acetic acid solution.

5. The method for preparing a fresh-keeping film according to claim 4, characterized in that: The mass fraction of acetic acid in the aqueous solution of acetic acid is 1wt%-2wt%; the mass ratio of glycerol to chitosan is 0.3-0.4:1; and the temperature of the water bath heating is 80°C-95°C.

6. The method for preparing a fresh-keeping film according to claim 1, characterized in that: The acetic acid solution of ascorbic acid carbon quantum dots and chitosan is stirred at a temperature of 75° C. to 80° C. to obtain a film-forming liquid, and the film-forming liquid is dried at a temperature of 75° C. to 80° C. to form a fresh-keeping film.

7. A fresh-keeping film, characterized in that: It is prepared based on the preparation method according to any one of claims 1 to 6.

8. An application of a cling film, characterized in that: The fresh-keeping film described in claim 7 is used for preserving fruits.

9. The use of a cling film according to claim 8, characterized in that: The fruit is one or more of strawberry, blueberry, grape and citrus.

Citation Information

Patent Citations

  • Relatively long emission wavelength fluorescent carbon quantum dot and preparation method thereof

    CN109097036A

  • Chiral carbon quantum dots and preparation method thereof

    CN109455692A

  • Preparation method of potato carbon quantum dots and degradable preservative film with high antibacterial activity

    CN114477138A

  • Preparation method and application of degradable preservative film based on walnut green seedcase

    CN118344631A

  • KR20220161024A

Cited By

  • Edible intelligent packaging film based on carbon dot doping as well as preparation method and application of edible intelligent packaging film

    CN120966067A